EFFECT ON THE PROCESSING OF EGG NUGGET CATFISH (Pangasius hypophthalmus) ACCEPTANCE OF USERS - Pusra, Wiwit; Sari, N. Ira; Loekman, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aimed to determine the effect of different types of eggs in processing of catfish nuggets of customer acceptance. The method used was experimental method by using a completely randomized design. The parameters tested are sensory (appearance, texture, odor and flavor), moisture content and protein content. The results showed that the level of acceptance by the customer, the catfish nuggets with egg is best treated with a level of customer acceptance is very fond of 62.4% and 37.6% like characteristics nuggets with egg which is colored in such a golden yellow, typical fish taste, chewy and slightly dry with little flavor fish specialties, with a water content of 11.29% and 57.40% protein.Keywords: eggs, nuggets, catfish, customer acceptance, organoleptic